Profitability of Companies in the Agricultural Sector Listed on the Indonesia Stock Exchange: The Role of Liquidity and Solvency - Satrio, Jaka; Kosim, Belliwati; Candera, Mister (Universitas muhammadiyah palembang, 2023)
The purpose of this study is 1) to determine the effect of liquidity and solvency on profitability in agricultural sector companies listed on the Indonesian Sharia Stock Index. 2) to determine the effect of liquidity on profitability in Agricultural Sector Companies listed on the Indonesian Sharia Stock Index. 3) to determine the effect of solvency on profitability in Agricultural Sector Companies listed on the Indonesian Sharia Stock Index. The population in this study amounted to 25 companies. The sampling technique uses purposive sampling so that the sample is 10 companies and 5 years. The data used in this study are secondary data that are publicly reported by the company. Data collection techniques in this study used the documentation method. This study uses multiple linear regression analysis techniques. The results showed that simultaneous or partial liquidity and solvency have a significant effect on profitability.